THE RENEWAL OF ROD AND CONE OUTER SEGMENTS IN THE RHESUS MONKEY - Young, Richard W. (The Rockefeller University Press, 1971)
The renewal of retinal rod and cone outer segments has been studied by radioautography in rhesus monkeys examined 2 and 4 days after injection of leucine-(3)H. The cell outer segment consists of a stack of photosensitive, membranous discs. In both rods and cones some of the newly formed (radioactive) protein became distributed throughout the outer segment. Furthermore, in rods (but not in cones), there was a transverse band of concentrated radioactive protein slightly above the outer segment base 2 days after injection. This was due to the formation of new discs, into which labeled protein had been incorporated. At 4 days, these radioactive discs were located farther from the outer segment base. Repeated assembly of new discs had displaced them away from the basal assembly site and along the outer segment. Measurements of the displacement rate indicated that each retinal rod produces 80–90 discs per day, and that the entire complement of outer segment discs is replaced every 9–13 days. To compensate for the continual formation of new discs, groups of old discs are intermittently shed from the apical end of the cell and phagocytized by the pigment epithelium. Each pigment epithelial cell engulfs and destroys about 2000–4000 rod outer segment discs daily. The similarity between visual cells in the rhesus monkey and those in man suggests that the same renewal processes occur in the human retina.